Effects of Phenyl Content and Molecular Structure on the Refractive Index of Organic Silicon Polymer - 朱淮军 戴子林 涂伟萍 (东华大学学报（英文版）, 2017)
The effects of phenyl content and group distribution on the refractive index of phenyl silicone oil were investigated by synthesis and characterization of silicone oils of different molecular structures.A group contribution function model was established to predict the refractive index. The results showed that refractive index of phenyl silicone oil increased as its phenyl content increased. A linear equation had been established to describe the quantitative relationship between the refractive index and phenyl content.Refractive index values from the group contribution function model showed good consistency with experimental results.